Nature attacks! - Tarshis, Lauren (Tarshis, Lauren. I survived true stories, 2015)
From 14-year-old Joseph Dunn who was the lone survivor of the Shark Attacks of 1916, to 9-year-old Mike Kramer who, with the help of his quick-thinking parents, survived the Peshtigo fire of 1871 (which took place on the very same day in history as the Great Chicago Fire!), to the 13-year-old girl who survived a terrifying attack by a box jellyfish, this is a collection of unforgettable narrative non-fiction stories of unimaginable destruction -- and, against all odds, survival.